MyCarRental.my: a conceptual solution - Ahmad Dahlan, Abdul Rahman; Ahmad, Muhamad Syazwan; Saifuddin, Muhamad Syahir; Mohd Adib, Muhammad Haziq; Hussen, Muhammad Zamir (Eclat Research Publication, 2015)
Due to the increasing public transport fee, the public tend to rent a car, since the rental fee is not controlled by the government and have no major hiking. But problems occur when there is bias, and limited contact access of car owners by customers. Car owners do not have platforms to advertise their cars. Emergency customers do not have their services rightly prepared. Certain specific methodology used to study and obtain data regarding the current car rental services industry in Malaysia. Literature reviews were conducted to study the current similar systems from all over the world. A web based car rental platform, called MyCarRental.my, is proposed to handle the car rental issues, challenges, supply, and demand in Malaysia. In proposing the MyCarRental.my conceptual solution, the Business Model Canvas (BMC) and Value Proposition Design (VPD) Canvas suite of tools were utilized.